Tolok Ukur Keluarga Sakinah Perspektif Mazhab Imam Syafi'i - Muhammad Amrullah; Muhammad Yassir (Cakrawala: Journal of Religious Studies and Global Society, 2025)
The family is a fundamental pillar in the development of civilization. In Islam, the concept of a sakinah (tranquil) family represents an ideal goal, grounded in spiritual, social, and legal values. This study aims to identify and formulate the criteria for a sakinah family based on the perspective of the Shafi’i school of thought. Using a library research approach, the study examines primary sources such as classical Shafi’i jurisprudence texts and relevant scholarly literature. The findings show that the Shafi’i school emphasizes the importance of a valid marriage contract, balance in the rights and responsibilities of husband and wife, proper child upbringing, respectful communication, and spiritual orientation within the household. These criteria reflect a holistic integration of moral values, Islamic law, and social needs. Although formulated in a medieval context, the principles of the Shafi’i school remain applicable in addressing contemporary challenges, such as domestic conflict, imbalance in family roles, and communication breakdowns. This research contributes significantly to the academic discourse on sakinah families and provides practical guidance for Muslims in Indonesia to build harmonious families in accordance with Islamic teachings